PERAN PETANI DALAM PENGELOLAAN AIR IRIGASI DI DESA OLLOT KECAMATAN BOLANGITANG BARAT KABUPATEN BOLAANG MONGONDOW UTARA (The Role of Farmers in Irrigation Water Management in Ollot Village, Bolangitang Barat District, North Bolaang Mongondow Regency) - Mita Saerang; Jenny Baroleh; Theodora M. Katiandagho (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
This study aimeds to determine the role of farmers in the of irrigation water management in Ollot Village, West Bolangitang District, North Bolaang Mongondow Regency. The study was carried out from March to April 2021. The data used in the study were in the form of primary and secondary data. Primary data were obtained from direct interviews with rice farmers using a questionnaire. Secondary data were obtained from the Ollot Village Office, as well as data related to research taken from the internet. Sampling was carried out by means of Simple Random Sampling as many as 30 samples.The results showed that the role of farmers in the management of irrigation water in Ollot Village was included in the category of â€œparticipateâ€. Farmers participated in two elements, namely utilizing irrigation water channels and maintaining irrigation channels. However, there were still farmers who â€œless participateâ€ in the maintenance part because there was no regulatory agency.